ACSS2 Promotes Proliferation and Invasiveness of Skov-3 and PA-1 Ovarian Cancer Cell Lines under Hypoxia - Mroweh, Ola (2024)
Ovarian cancer is the eighth most common malignancy among women worldwide. Despite advances in treatment, rising cases of chemoresistance and associated morbidity continue to pose significant challenges, highlighting the urgent need to identify novel therapeutic targets. The tumor microenvironment presents a hostile context for cancer cells, compelling them to undergo metabolic rewiring and adaptation to ensure survival. Acetate-dependent acetyl-CoA synthase 2 (ACSS2), a critical cytosolic enzyme, translocates to the nucleus in response to cellular stress. Given its essential metabolic and regulatory roles, ACSS2 has emerged as a key player in promoting cancer progression, particularly under metabolic stress conditions such as hypoxia. However, its role in ovarian cancer remains unexplored. This study aims to elucidate the role of ACSS2 in ovarian cancer progression under hypoxic conditions. Immunohistochemistry was performed on ovarian cancer tissue samples, including High Grade Serous Ovarian Carcinoma (HGSOC), and control tissues, to evaluate ACSS2 expression and localization. Ovarian cancer cell lines (Skov-3 and PA-1) were treated with an ACSS2 inhibitor under normoxic and hypoxic conditions and functional assays, including proliferation, colony formation, migration, invasion, and three-dimensional spheroid growth, were conducted. The impact of ACSS2 inhibition on key signaling pathways, including PI3K and HIF, was analyzed using RT-qPCR and Western blot. We observed that ACSS2 was overexpressed and predominantly localized to the nucleus in HGSOC tissues, with significantly higher H-scores compared to low-grade and normal tissues. ACSS2 inhibition impaired proliferation, colony formation, and spheroid growth in both cell lines, with greater sensitivity observed under hypoxic conditions. Migration and invasion assays revealed that ACSS2 inhibition significantly reduced cellular motility and invasiveness, particularly in hypoxia. Mechanistic studies demonstrated that ACSS2 inhibition modulates the PI3K pathway and downregulates HIF-responsive genes, suggesting its role in metabolic adaptation and tumor progression. ACSS2 is a critical regulator of ovarian cancer growth and invasiveness, particularly under hypoxic stress. Targeting ACSS2 may represent a promising therapeutic strategy for managing HGSOC. Further studies are warranted to evaluate its clinical potential.